(untitled) (Bangladesh Journal of Medical Science, 2021)
Hajj pilgrimage is a nobligation for every Muslim that must be carried out at least once in their lifetime. Every year, more than 3 million pilgrims from over 180 countries travel to worship within a confined area of twelve kilometres in Makkah, Kingdom of Saudi Arabia (KSA). The host country and participating countries need to institute effective measures for a safer and healthier Hajj pilgrimage. In the immediate Hajj season during the COVID-19 pandemic, the number of pilgrims need to be reduced to the optimum number that can be managed individual countries’ Hajj missions. Beside proof COVID-19 clearance before travelling and completed Covid-19 vaccination, the stay in KSA should be shortened for Hajj ritual only. The participating countries responsible to thoroughly select individuals with low risk of severe infections, provide health education program, offer all compulsory and recommended vaccines and allocate adequate healthcare/isolation centres in KSA. The participating countries are also liable to prepare adequate quarantine places for hajj pilgrims when returning home. Individual pilgrims are responsible to prevent respiratory pathogens from spreading. Prior to departure for Hajj, they need to undergo a thorough medical examination, received all compulsory and recommended vaccines and follow health education program. During Hajj, they need to follow instructions by Hajj authorities, practicing proper hygiene, wearing a face mask and avoid crowded places. They also need to report to countries’ Hajj mission healthcare if having any fever or respiratory syndromes. With adequate measures prior, during and post-Hajj, we hope health security risk during the next Hajj seasons will be minimized. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.732-740